Evaluasi Rangka Beton Bertulang Dengan Dinding Geser Menggunakan Fema 310 (Studi Kasus Pada : Gedung Menara Dang Merdu Bank Riau) - Muhammad Rizky; Alex Kurniawandy; Zulfikar Djauhari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The earthquake is a natural disaster that is very difficult to predict the time and location of occurrence. A relatively short process very inversely proportional to the impact. Planning for building must be considered for anticipated damage that will occur as a result of an earthquake. This study aims to conduct a thorough evaluation of the performance of the structure of the Building Dang Merdu Tower of Bank Riau against earthquake hazards by using the FEMA 310 document. The evaluation was conducted on the evaluation of the first phase of the checklist method FEMA 310, the second phase of evaluation with linear static methods and evaluation of the third phase of the method static nonlinear (pushover). Based on FEMA checklist Building Dang Merdu Tower of Bank Riau does not meet the requirements at the soft story investigation. Stiffness of the first level of less than 70% on the stiffness of the second level. Based on a linear static analysis for equivalent static earthquake load story drift value does not meet the requirements story drift permit SNI 1726-2012 while the earthquake response spectrum meet the requirements. Based on the pushover analysis level of the performance Building Dang Merdu Tower of Bank Riau is O (Operational) on ATC-40.Keywords: FEMA 310, linear static, pushover, performance of the structure, inelastic drift